KEDUDUKAN WASIAT SEBAGAI INSTRUMEN DALAM PERUBAHAN HUKUM KELUARGA DI INDONESIA - HERU PURWADI HADIJANTO (Universitas Slamet Riyadi, 2008)
ABSTRACT The last will (wasiat) of deceased person is a part of law regulation that conducted by society. This regulation gene rally has been introduced by Islamic law and other system of law in Indonesia. The will according to fight is only one side’s action and it becomes charity agreement, meanwhile according to Al-Qur’an and prophet tradition, the position of the will constitutes integrative position in term of Islamic inheritance law. For that reason, it needs reinterpreting so that the will becomes as an instrument to change family law in Indonesia. Keywords : Last will, Figh, Indonesia, Family of Law.